Does being a refugee affect prognosis in patients who underwent surgery due to peptic ulcer perforation? - Citlak, Gamze; Yurtteri, Mustafa Ertugrul; Soytas, Yigit; Yuksel, Sercan; Dincer, Mursit; Ferlengez, Ekrem (Turkish Assoc Trauma Emergency Surgery, 2020)
BACKGROUND: Although Turkey hosts the largest number of Syrian immigrants, the interpretation of their health problems seems to be inadequate and understudied. In this study, we aimed to investigate whether being a refugee is a prognostic factor or not for peptic ulcer perforation (PUP). METHODS: A retrospective study was designed in Turkish Citizen patients and the refugees to compare the prognosis who underwent surgery for PUP. After ethical committee approval, the data of 143 patients, constituting 130 males and 13 females, operated for PUP, were collected. Patients' files, surgery notes and outpatient policlinic data were evaluated. RESULTS: In this study, 105 patients were Turkish Citizen, while the remaining 38 patients were refugees. Eight (7.6%) Turkish and one (2.6%) refugee patient died. There was no statistical significance between the two groups concerning mortality (p=0.445). Age, perforation diameter and localization, need of reoperation, nasogastric tube detention time, CRP, hematocrit, albumin, creatinine, BUN levels were found statistically significant for mortality. CONCLUSION: Although being a refugee has been identified as a risk in the etiopathogenesis of peptic ulcer disease, we found that being a refugee in Turkey is not a negative prognostic factor for PUP.
Peptik ülser perforasyonunun cerrahi tedavisinde mülteci olmak prognozu etkiler mi? Geriye dönük klinik çalışma
Keywords: Morbidity; mortality; peptic ulcer perforation; refugee